Jurisdiction of federal court to hear and determine appeals - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2014)
The focus of this article is concerning the jurisdiction of the Federal Court to hear and determine an appeal against the decision of the Court of Appeal in respect of any criminal and civil cause or matter. Reference is made to the recent Federal Court’s decision in Siow Chung Peng v PP[2014]4 MLJ 504 where in this case, the Federal Court was faced with the issue of whether it has the jurisdiction to hear criminal appeals when the matter had originated from a subordinate court. The determination of the above issue is necessary as this would ascertain the Federal Court’s jurisdiction to entertain such applications in the future.